Evaluasi Kinerja Crushing Plant untuk Mencapai Target Produksi Batu Andesit di PT Lotus SG Lestari, Desa Cipinang, Kecamatan Rumpin, Kabupaten Bogor, Provinsi Jawa Barat - Kharisma Nur Azis; Sriyanti; Noor Fauzi (UNISBA Press, 2022)
Abstract. Processing andesit in crushing plant PT Lotus SG Lestariconsists of five stages where for these stages, ranging from pumping, primary crushing, secondary crushing,tertiary crushing to sizing. Alat used 1 unit jaw crusher with the brand metso c140 (primary crushing) and 1 unit cone crusher with cmc pc brand (secondary crushing) and also 2 units cone crusher with brand trimax machinery nh400 (tertiary crushing). Alat Crushing,forandesite processing units is also supported by supporting tools which include hopper, 1 unit grizzly feeder with brand trimax machinery ad plus (feeding), 4 units vibrating scren with brand trimax ad plus,and 19 belt conveyors,to find out the workefficiency of the crushing plant itself is seen the effective time of crushing plant and also from the time of obstacles obtained from crushing plant such as stand by and also repair from it can be obtained also about the condition of mechanical devices such as value mechanical availability, physical availability, use of availability, effective of utilization and to find out the amount of production obtained from the crushing plant is by using the belt cutmethod, so that with this belt cut method in addition to knowing the amount of production, can know the loose material,and production rate index from each crushing planttool. Abstrak. Pengolahan andesit pada crushing plant PT Lotus SG Lestari ini terdiri dari lima tahapan dimana untuk tahapan tersebut yaitu mulai dari pengumpanan, primary crushing, secondary crushing, tertiary crushing hingga pada sizing. Alat yang digunakan 1 unit jaw crusher dengan merk metso c140 (primary crushing) dan 1 unit cone crusher dengan merk cmc pcc4a (secondary crushing) dan juga 2 unit cone crusher dengan merk trimax machinery nh400 (tertiary crushing). Alat Crushing, untuk unit pengolahan andesit ini juga didukung alat penunjang yang diantaranya yaitu hopper, 1 unit grizzly feeder dengan merk trimax machinery ad plus (pengumpanan), 4 unit vibrating scren dengan merk trimax ad plus, dan 19 belt conveyor, untuk mengetahui efisiensi kerja dari crushing plant tersendiri yaitu dilihat dari waktu efektif crushing plant dan juga dari waktu hambatan yang didapatkan dari crushing plant seperti stand by dan juga repair dari hal tersebut dapat diperoleh juga mengenai kondisi alat mekanis seperti nilai mechanical availability, physical availability, use of availability, effective of utilization dan untuk mengetahui jumlah produksi yang diperoleh dari crushing plant tersebut yaitu dengan menggunakan metode belt cut, sehingga dengan metode belt cut ini selain mengetahui jumlah produksi, dapat mengetahui loose material, dan production rate index dari masing – masing alat crushing plant.